The coal truth : the fight to stop Adani, defeat the big polluters and reclaim our democracy - Ritter, David (UWA Publishing, 2018)
Since 2012, the fight to stop the opening of the vast Galilee coal basin has emerged as an iconic pivot of the Australian climate and environment movement. The Coal Truth: the fight to stop Adani, defeat the big polluters and reclaim our democracy provides a timely and colourful contribution to one of the most important struggles in our national history - over the future of the coal industry. Written by an environmental insider with an eye on the world his daughters will inherit, The Coal Truth is told with wit and verve, drawing in other specialist voices to bring to life the contours of a con.